"Caught Between a Rock and a Hard Place"—Between Discourses of Empowerment and Solicitude: Danish Public Sector Service Professionals' Discourses of Nonattendance. (September 2017) - Hoej, Michaela; Johansen, Katrine Schepelern; Olesen, Birgitte Ravn; Arnfred, Sidse Marie
Nonattendance constitutes a profound challenge in public sector services targeting young adults with mental health difficulties. Therefore, researchers and practitioners are occupied with trying to resolve this. For clinicians to be aware of their own naturalized and perhaps inappropriate communicative practices, we investigated the established normative organizational logics behind explanations and strategies related to nonattendance. We performed a critical discourse analysis on material collected through participatory research throughout 2015. Three discourses were identified: solicitude, responsibility, and youth discourse. Although the discourses were complex and entangled, they were used by all practitioners. Furthermore, some of the discourses, especially the responsibility and the solicitude discourses, were inherently tension filled, and practitioners experienced frustration in dealing with these tensions. The youth discourse can be understood as a coping mechanism to deal with these tensions because it distributes responsibility for nonattendance to general social and cultural processes.